Pengaruh Latihan Shuttle Run Terhadap Kemampuan Dribbling Siswa Ekstrakurikuler Futsal Di SMPN 2 Lahat Selatan - Dimas Arafi Syahiri; Ilham Arvan Junaidi; Hengki Kumbara (CV. Ulil Albab Corp, 2026)
The background of this study is the low dribbling ability of extracurricular futsal students at SMPN 2 Lahat Selatan. The purpose of this study is none other than to determine the improvement of students' dribbling ability in futsal games through the shuttle run training method. Based on the results of the study, it was found that training using the shuttle run training method had an effect on the dribbling ability of extracurricular students at SMPN 2 Lahat Selatan. This study was conducted on 24 extracurricular students at SMPN 2 Lahat Selatan who were used as samples. There is an effect of shuttle run training on the dribbling ability of extracurricular students at SMPN 2 Lahat Selatan. This can be seen from the average pre-test time score of 19.86 seconds which decreased to 19.62 seconds at the post-test. The difference in the average score of 0.24 centimeters indicates an increase in dribbling ability. The results of the paired sample t-test showed a calculated t-value of 3.917 > t-table of 1.717 with a significance value of 0.001 < 0.05, indicating a difference in dribbling ability during the pretest and posttest. Thus, the shuttle run training method provides positive results in improving students' dribbling ability in futsal. This training can be used as an alternative teaching method or training program in futsal extracurricular activities at school.